2017
DOI: 10.1103/physrevlett.118.113601
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Resonances in Light Scattering from Two-Dimensional Atomic Arrays

Abstract: We consider light scattering off a two-dimensional (2D) dipolar array and show how it can be tailored by properly choosing the lattice constant of the order of the incident wavelength. In particular, we demonstrate that such arrays can operate as nearly perfect mirrors for a wide range of incident angles and frequencies close to the individual atomic resonance. These results can be understood in terms of the cooperative resonances of the surface modes supported by the 2D array. Experimental realizations are di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
278
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 267 publications
(299 citation statements)
references
References 52 publications
9
278
0
Order By: Relevance
“…The growing throughput of computers available to researchers is making such a plan practical. These methods, whether called classicalelectrodynamics simulations or coupled-dipole simulations, are now a routine theoretical tool [2,4,7,8,[14][15][16][17][18][19][20][21][22][23][24][25][26]. Closely related numerical techniques based on the analysis of the eigenstates of the coupled system of the light and the atoms [15,[27][28][29][30][31][32] or density matrices and quantum trajectories [33][34][35] are also widely used today.…”
Section: Introductionmentioning
confidence: 99%
“…The growing throughput of computers available to researchers is making such a plan practical. These methods, whether called classicalelectrodynamics simulations or coupled-dipole simulations, are now a routine theoretical tool [2,4,7,8,[14][15][16][17][18][19][20][21][22][23][24][25][26]. Closely related numerical techniques based on the analysis of the eigenstates of the coupled system of the light and the atoms [15,[27][28][29][30][31][32] or density matrices and quantum trajectories [33][34][35] are also widely used today.…”
Section: Introductionmentioning
confidence: 99%
“…Their miniaturization is fundamentally limited by the optical wavelength in the case of dielectric mirrors and photonic crystals (1) or by the skin depth for metallic mirrors (2). Recently, resonant scattering has emerged as a method for overcoming these limitations and for controlling light at the atomic scale (3)(4)(5)(6)(7)(8)(9)(10)(11). For instance, highly reflective mirrors based on individual quantum emitters have been demonstrated by coupling them to optical cavities and nanophotonic waveguides (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…These narrow linewidths have a dominant contribution from radiative decay of ∼1.5 meV for MoSe 2 [11,12]. Motivated by these developments, we previously analyzed the optical response of a monolayer TMD theoretically [13] and showed that it realizes an atomically thin mirror [13][14][15].…”
mentioning
confidence: 99%